Efektivitas Pemberian Kombinasi Tempe Kedelai Daun Kelor dan Tablet Fe Dibandingkan dengan Pemberian Tablet Fe terhadap Peningkatan Kadar Hemoglobin pada Remaja Putri dengan Anemia - Olgaliana, Deswimar Olgaliana; Handayani, Lulut; Rahmawati, Wiwin Renny; Isworo, Adi (Dinasti Research, 2025)
Anemia is a condition where the number of red blood cells is insufficient to meet the body's physiological needs. Anemia is prone to occur in adolescence. The prevalence of anemia in the world ranges from 40-88% of 600,000,000, while in Indonesia it is 48.9% of 25,000,000. Anemia in adolescent girls has a negative impact not only on academic achievement but can also increase the risk of pregnancy complications and disrupt fetal growth and development. Symptoms of anemia are characterized by 5L (Weak, Tired, Lethargic, Exhausted, Negligent). Efforts are made to overcome this condition by consuming nutritious foods (containing iron) in the form of moringa leaf soybean tempeh and taking Fe tablets. This study aims to determine the effectiveness of administering a combination of moringa leaf soybean tempeh and Fe tablets or Fe tablets alone on hemoglobin levels in adolescent girls with anemia. This study is a quasi-experimental study with a two-group pretest-posttest design. The population is 95 adolescent girls with a sample size of 24 respondents. This study was conducted in May 2025 at the Al Itqon Islamic Boarding School in Semarang City. The instrument in this study used a digital hemoglobin device that has been tested for validity and reliability. Hypothesis testing used the Independent t-test. The average hemoglobin level in the intervention group increased from 10.6 gr/dl before treatment to 14.6 gr/dl after treatment, while in the control group it increased from 10.5 gr/dl to 12.6 gr/dl after treatment. Both treatments showed an effect between the combination of moringa leaf soybean tempeh and Fe tablets with the administration of Fe tablets alone, but the administration of the combination of moringa leaf soybean tempeh and Fe tablets proved more effective in increasing hemoglobin levels in adolescent girls with anemia compared to the administration of Fe tablets alone.